Healing foods : cooking for celiacs, colitis, Crohn's and IBS : over 200 recipes for the Specific Carbohydrate Diet - Ramacher, Sandra (Noosaville, Qld. : Elephant Publishing, 2007)
A year in the making, Sandra Ramacher has released Healing Foods: Cooking for Celiacs, Colitis, Crohns and IBS, a visually stunning and intelligently written cookbook. It is specifically designed to please and inspire all those who suffer from these debilitating intestinal diseases, as well as those who already live happier lives thanks to the Specific Carbohydrate Diet (TM). This book strictly adheres to the diet prescribed by Elaine Gottschall in her revolutionary book Breaking The Vicious Cycle. The Specific Carbohydrate Diet is a strict grain-free, lactose -free, and sucrose-free dietary regimen intended for those suffering from Crohn's disease, ulcerative colitis, celiac disease, diverticulitis, inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS).
Title from cover.
"Totally grain free, gluten free, sugar free, and lactose free"
Includes index.
Keywords: Carbohydrate intolerance -- Diet therapy -- Recipes; Gluten-free diet -- Recipes; Wheat-free diet -- Recipes; Intestines -- Diseases -- Diet therapy -- Recipes; Inflammatory bowel diseases -- Diet therapy -- Recipes; Colon (Anatomy) -- Diseases -- Diet therapy -- Recipes; Food allergy -- Diet therapy -- Recipes